Is educational expansion beneficial for health? A counterfactual mediation analysis of its impact on trends of daily activity limitations among different age groups in Germany - Batoul Safieddine; Johannes Beller; Stefanie Sperlich (Archives of Public Health, 2026)
Abstract Background Education has been a well-established indicator of health. Against the background of educational expansion, little is known on how the temporal rise in educational attainment is affecting health trends. This study mainly examines the mediation effect of educational expansion on the trends of limitations in daily activity as measured by the global activity limitation indicator (GALI). Methods The study utilized data from the German Health Update survey (GEDA) using five waves between 2008 and 2024. Predicted probabilities and trends of (severe) limitation in daily activities were estimated using logistic regression analyses. Educational inequalities in the rates of limitation in daily activities in the five waves as well as their development over time were examined using the slope and relative indices of inequalities (SII, RII). Causal mediation analyses were applied to examine how educational expansion influenced the temporal development of (severe) limitations. All analyses were stratified by gender and three age groups. Results The results reveal significant disparities in severe limitations in daily activities, particularly widening among the middle-aged group. The findings show divergent trends in limitation across age groups: older individuals have experienced considerable improvements, while younger individuals have experienced an increase in severe limitations over time. In both cases, educational expansion was found to have a positive mediating effect on the temporal development of (severe) limitations, reducing the exacerbation in younger individuals and contributing to the improvement in older individuals. Conclusion Educational expansion appears to have a positive influence on health trends, which reinforces the need for continued educational reforms. More focus is needed on younger individuals to explore factors behind their declining health. Additionally, addressing widening educational inequalities, particularly among middle-aged adults, is crucial for narrowing the gap between educational groups. Social challenges and the digital divide could be important contextual factors to address this development.